Correction: Modulating the electron-transfer properties of a mixed-valence system through host–guest chemistry. Issue 7 (15th July 2015) - Zubi, Ahmed; Wragg, Ashley; Turega, Simon; Adams, Harry; Costa, Paulo J.; Félix, Vítor; Thomas, Jim A.
<x xml:space="preserve">Abstract</x> Correction for 'Modulating the electron-transfer properties of a mixed-valence system through host–guest chemistry' by Ahmed Zubi et al., Chem. Sci., 2015, 6, 1334–1340.